Islamic Aspects Of Interest: Financing Strategy - Sadeghzadeh, Akbar (The International Journal of Accounting and Business Society, 2004)
Allah made trade lawful and forbade ribaâ€ (the Holy Quran 2:275). Islamic literature interprets â€œribaâ€ to â€œinterestâ€. Moslims perceive interest forbidden and avoid it. This affects adversely money and capital markets. ï¬scal and monetary policies. financing projects and eventually growth strategies and causes worse economic conditions of even rich Moslim countries. Many research projects, dealing with various aspects of rihu have been carried out aiming at ï¬nding a solution to the problem. Most of these pojects deal with deferral charges imposed on overdue loans, perceiving this charge as a penalty. hence legal; while some scholars declare it as unlawful and reject it. Interest, however, consists of three elements. These elements are: â€œtime value of money premium (Itvp)". â€œrisk premium (lrp)" and â€œinï¬‚ation premium (lip)â€. Therefore, the following equation establishes: l = Itvp + lrp + lip. The Itvp is the same for all classes of borrowers and is almost constant. lrp and lip, however, are functions of â€œthe riskiness of the loanâ€ and â€œthe inï¬‚ationary conditions of economyâ€, respectively. This article intended to analyse each element as well as their mixture from an Islamic point of view in order to clarify which element of interest best matches with the meaning of riba, what types of transactions fall within this domain (hence are forbidden); and what types fall Â